Developing Reading Materials for Sport Science Sophomores - Eny Suspartiana; Mirjam Anugerahwati; Suharmanto Suharmanto (Jurnal Pendidikan Humaniora, 2015)
Abstract: This study aims to develop reading materials for the Sport Science Sophomores of Univer-sitas Negeri Malang due to the unavailability of the materials. The design of her research is R and D (Research and Development) simplified from Borg and Gall design (1983). The result of preliminary study showed that the available materials were not in line with the syllabus since it still reflects the teaching of General English, while the syllabus emphasizes teaching English texts related to Sport Science. The final products of this research are ‘Student’s Book and Teacher’s manual’.Key Words: reading materials, sophomores, sport scienceAbstrak: Penelitian ini bertujuan untuk mengembangkan bahan bacaan untuk mahasiswa tingkat 2 jurusan Ilmu Keolahragaan di Universitas Negeri Malang karena tidak tersedianya bacaan bahan ajar. Desain penelitiannya adalah R dan D (Penelitian dan Pengembangan) yang disederhanakan dari  desain Borg dan Gall. Hasil penelitian pendahuluan menunjukkan bahwa bahan yang tersedia tidak sesuai dengan silabus karena masih mencerminkan ajaran Bahasa Inggris umum, sementara silabus menekankan pengajaran teks bahasa Inggris yang berhubungan dengan Sains Sport. Produk akhir dari penelitian ini adalah ‘Buku Siswa dan manual Guru’.Kata kunci: bahan bacaan, mahasiswa tingkat dua, ilmu keolahragaan